Benefits from the implementation of project tasks with the use of virtual team - Barnowska Beata; Kozaryn Maciej (Management)
The necessity of customer oriented approach, the ability of quick adapting to changing demand and the expectations of reducing project costs have recently resulted in a strong development of cooperation between various organizations implementing joint ventures. Projects-oriented organizations, creating virtual project teams, have become more and more popular. Dissemination of this organizational form has induced the authors to consider the real benefits achieved by enterprises using virtual project teams to implement projects. The purpose of the article was to try to calculate the benefits that companies can obtain when implementing projects, by replacing traditional project teams with virtual project teams (ceteris paribus). The presented research results show the possibility of achieving significant financial benefits due to the use of virtual project teams to carry out the projects implemented in many units with a large geographical dispersion.